1998
DOI: 10.1021/bi9817360
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Absorption Spectroscopy on Layered Photosystem II Membrane Particles Suggests Manganese-Centered Oxidation of the Oxygen-Evolving Complex for the S0-S1, S1-S2, and S2-S3 Transitions of the Water Oxidation Cycle

Abstract: By application of microsecond light flashes the oxygen-evolving complex (OEC) was driven through its functional cycle, the S-state cycle. The S-state population distribution obtained by the application of n flashes (n = 0. 6) was determined by analysis of EPR spectra; Mn K-edge X-ray absorption spectra were collected. Taking into consideration the likely statistical error in the data and the variability stemming from the use of three different approaches for the determination of edge positions, we obtained an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
206
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(233 citation statements)
references
References 24 publications
24
206
0
3
Order By: Relevance
“…This change, supported by results of earlier and later XANES spectra (33), led to the conclusion that an oxygen rather than a manganese is oxidized in this transition, which strongly affected the suggested O-O bond formation mechanism (34,35). The conclusion from the XANES spectra has been questioned experimentally (36), and also recently on the basis of DFT model calculations (37). The Dau and coworkers results, however, gave one change from a distance larger than 3.0 Å down to 2.77 Å; this led to a suggested structural change in this transition with a formation of an additional Mn-Mn bis-μ-oxo bridge in S 3 (38).…”
Section: Resultsmentioning
confidence: 82%
“…This change, supported by results of earlier and later XANES spectra (33), led to the conclusion that an oxygen rather than a manganese is oxidized in this transition, which strongly affected the suggested O-O bond formation mechanism (34,35). The conclusion from the XANES spectra has been questioned experimentally (36), and also recently on the basis of DFT model calculations (37). The Dau and coworkers results, however, gave one change from a distance larger than 3.0 Å down to 2.77 Å; this led to a suggested structural change in this transition with a formation of an additional Mn-Mn bis-μ-oxo bridge in S 3 (38).…”
Section: Resultsmentioning
confidence: 82%
“…PSII-enriched membrane fragments were prepared as described previously (13). The protocol for the preparation of n-octyl-␤-D-glycosidesolubilized PSII core particles ("OG cores") and PSII core dimers described by Hankamer et al (14) was modified in that the osmoprotective agent glycine betaine (GlyB) was used throughout the preparation.…”
Section: Methodsmentioning
confidence: 99%
“…However, on the basis of Mn K-edge studies, other groups have proposed that Mn is oxidized during the S 0 →S 1 , S 1 →S 2 , and also during the S 2 →S 3 transitions. 17,18 The requirement of a higher signal-to-noise ratio for the EXAFS relative to the XANES experiments has made EXAFS measurements more difficult for the flash-induced S state samples. Earlier EXAFS data from the chemically treated S 3 state samples produced by a double-turnover method indicated that the two di-μ-oxo-bridged Mn-Mn dimer units may become nonequivalent.…”
Section: Introductionmentioning
confidence: 99%